Long-chain PUFA profiles in parental diets induce long-term effects on growth, fatty acid profiles, expression of fatty acid desaturase 2 and selected immune system-related genes in the offspring of gilthead seabream. Issue 1 (3rd July 2019) - Turkmen, Serhat; Hernández-Cruz, Carmen M.; Zamorano, María J.; Fernández-Palacios, Hipólito; Montero, Daniel; Afonso, Juan M.; Izquierdo, Marisol
Abstract: The present study investigated the effects of nutritional programming through parental feeding on offspring performance and expression of selected genes related to stress resistance in a marine teleost. Gilthead seabream broodstock were fed diets containing various fish oil (FO)/vegetable oil ratios to determine their effects on offspring performance along embryogenesis, larval development and juvenile on-growing periods. Increased substitution of dietary FO by linseed oil (LO) up to 80 % LO significantly reduced the total number of eggs produced by kg per female per spawn. Moreover, at 30 d after hatching, parental feeding with increasing LO up to 80 % led to up-regulation of the fatty acyl desaturase 2 gene ( fads2 ) that was correlated with the increase in conversion rates of related PUFA. Besides, cyclo-oxygenase 2 ( cox2 ) and TNF-α ( tnf-α ) gene expression was also up-regulated by the increase in LO in broodstock diets up to 60 or 80 %, respectively. When 4-month-old offspring were challenged with diets having different levels of FO, the lowest growth was found in juveniles from broodstock fed 100 % FO. An increase in LO levels in the broodstock diet up to 60LO raised LC-PUFA levels in the juveniles, regardless of the juvenile's diet. The results showed that it is possible to nutritionally programme gilthead seabream offspring through the modification of the fatty acid profiles of parental diets to improve the growth performance of juveniles fed low FO diets, inducing long-term changes in PUFA metabolism with up-regulation of fads2 expression. The present study provided the first pieces of evidence of the up-regulation of immune system-related genes in the offspring of parents fed increased FO replacement by LO.